PERAN ORANGTUA TUNGGAL (BAPAK) DALAM MENGASUH ANAK (STUDI MASYARAKAT KELURAHAN SIALANG SAKTI KECAMATAN TENAYAN RAYA KOTA PEKANBARU PROVINSI RIAU - Iska Merlinta Sinamo; Swis Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research uses descriptive qualitative method or research which the end result gives a deep understanding. The source of the data used are primary and secondary data obtained through interviews conducted by researchers, as well as presented by the city information committee as a reinforcement of the research result. Data will be analyzed by descriptive analysis method. With social action theory and role theory as a theoretical foundation in research.The results of this study are the role of fathers as single parents in caring for their children in the ward sialang sakti namely: 2 single parent fathers apply democratic parenting, and 2 single parent parents apply permissive parenting and 1 single parent apply otoriter parenting. Parenting that is applied differently to children gives rise to different behaviors in children, children who are cared for by democratic parenting are more responsible, warmer and more independent, children in foster care with permissive parenting are less responsible and rebellious and children in fosten care with otoriter parenting are more quite, shy and obedient. Keywords: rule, parenting, single parent father, child.